Sistem Penyimpanan Arsip Berbasis Web Menggunakan Phprad Classic Pada Kantor Wali Nagari Salo Kecamatan Baso - Novadilastri, Novadilastri; Yoyet, Eva; Jumyetti, Jumyetti; Putra , Aulia Darma (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Archives are documents relating to the administration and archiving of government activities carried out at the Wali Nagari Salo Office. Various documents include letters and certificates. Manual recording sometimes results in unclear writing in the agenda book, making it difficult to process the data. One solution to overcome problems and simplify archive management is through designing a digital archive system that can overcome problems regarding archive management. PHPRad Classic is a sophisticated, fast application development program combined with MySQL, which is a database processing system that can process various types of data and produce the final result in the form of a report with a more attractive appearance that can be accessed via the internet network. Data was collected through interviews with the Nagari Secretary and Administrative staff of the Wali Nagari Salo Office. Data was also collected by making direct observations in the archives at the Wali Nagari Salo office.